2016
DOI: 10.1080/02755947.2015.1103820
|View full text |Cite
|
Sign up to set email alerts
|

Age and Growth of Atlantic Sturgeon in the New York Bight

Abstract: Accurate estimates of age and growth of fishes are important in the management and conservation of species and for the development of modeling approaches. Assessments of endangered or rare species typically are limited by poor or inadequate data owing to low abundance, unrepresentative sampling, and/or restrictions on sampling. Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus, which occurs along the east coast of North America, has five distinct population segments (DPSs) listed under the U.S. Endangered Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…() and is under the 5% level, as has been observed in other Atlantic Sturgeon aging studies (4.8% in Stevenson and Secor ; 3;.78% in Dunton et al. ). Reported age agreement between readers varies among sturgeon species (Rien and Beamesderfer ; Morrow et al.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…() and is under the 5% level, as has been observed in other Atlantic Sturgeon aging studies (4.8% in Stevenson and Secor ; 3;.78% in Dunton et al. ). Reported age agreement between readers varies among sturgeon species (Rien and Beamesderfer ; Morrow et al.…”
Section: Discussionsupporting
confidence: 75%
“…The Atlantic Sturgeon of the Hudson River are part of the New York Bight Distinct Population Segment (Dunton et al. ). Given the long history of data collection from the Atlantic Sturgeon fishery in the Hudson River, it has one of the only two adult spawning population estimates along the East Coast, at roughly 850 adults (ASSRT ; Kahnle et al.…”
mentioning
confidence: 99%
“…; Gervelis and Natanson ; Dunton et al. ). Studies would be improved if authors routinely documented potential size biases of their samples with the same care given to the methods used to age specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Tagged sturgeon ranged from 57 to 181 cm fork length at time of release, corresponding to ages 3–24 (Dunton et al . ). Genetic analysis of fin clips revealed that 77% of tagged fish were of Hudson River origin and 87·7% were of New York Bight Distinct Population Segment origin (O'Leary et al .…”
Section: Methodsmentioning
confidence: 97%